Falling off the Radar? Reaching Out to the Finnish Roma Community during the COVID-19 Pandemic - Marko Stenroos; Laura Musta; Natalia Skogberg (Social Sciences, 2023)
In this paper, we ask how the Finnish Roma community handled the challenging times of the COVID-19 pandemic, and how the information reached Roma communities. The previous studies indicate existing health inequalities between Finnish Roma and the general population. The point of departure for the article is crisis communication between Finnish Roma and national authorities. The themes of racialization, mistrust and Roma relying on peers as a source of information and support became apparent. From this setting, this article sheds light on the way of speaking, usage of language, (Finnish) as a social construction of ethnic identity and expression of (non)belonging. At the same time, the usage of languge and codeswitching reveals social stratifications among the Finnish Roma population. Findings indicate that subtle forms of exclusion of Roma prevail in Finland and are materialized as a “left alone mentality”. Consequently, Roma persons working as civil servants or NGO workers would potentially constitute a crucial link between health authorities and the Roma population. This link, however, should be constantly maintained. The study is a qualitative study and based on thematic interviews among Roma actors.